Powdery Mildews in the Libyan Jamahiriya: IV. Identity of certain powdery mildew fungi - KHAN, M. WAJID (The Libyan Journal of Agriculture, 2023)
This paper is fourth in the series based on studies made to enlist and identify powdery mildew species infecting cultivated and wild plants in the Libyan Jamahiriya. It includes Sphaerotheca erodii. Sphaerotheca fuliginea, Sphaerotheca pannosa, Erysiphe hetae. Erysiphe galeopsidis. Erysiphe graminis, Erysiphe polygoni, Erysiphe heraclei, Erysiphe convolvuli and Podosphaera oxyacanthae var. tridactyla on certain hosts not described in this series. S. erodii, E. betae and E. galeopsidis are new to the powdery mildew flora of the Libyan Jamahiriya. S. erodii was recorded on Erodium malacoides and Erodium laciniatum; E. hetae on Beta vulgaris var. cicla; and E. galeopsidis on Lamium amplexicaule. The occurrence of £. graminis on Avena barbat a. Avena eriantha and Lophochloa cristata and S. fuliginea on Bidens bipinnata are new world records. The records of E. graminis on Poa pratensis, E. polygoni on Polygonum equisetiforme, E. heraclei on Foeniculum vulgare and E. convolvuli on Ipomea hederacea are new to this country.